Optimizing Liquidity Management in Islamic Banks: A Risk and Shariah Compliance Perspective - Nikmah, Lailatun; Tri Wahyuni, Nelly Rizka; Kharisma, Weka Nur; Zunaidi, Arif (Syari'ah Economics, 2025)
This study aims to determine the concept and role of optimizing liquidity management in Islamic banks. Liquidity management is a very important aspect of Islamic bank operations. Adequate liquidity is needed to meet short-term obligations and support business growth. The purpose of optimizing liquidity management, analyzing the concept and role of optimizing liquidity management in Islamic banks in Indonesia, given the importance of liquidity management in Islamic banks lies in its ability to meet financial obligations without violating sharia principles, so strategic steps are needed to anticipate liquidity risk. The method used in this study is conceptual analysis through literature review on liquidity strategy and funding structure in Islamic banks. The main findings indicate that effective liquidity management does not only focus on short-term aspects, but also includes long-term strategies related to funding structure, which is important for the sustainability and stability of the bank. The conclusion of this study is that liquidity management is a crucial foundation for the operations of Islamic banks. The effectiveness of this management not only ensures the fulfillment of short-term obligations in accordance with sharia principles, but also maintains customer confidence, mitigates risk, optimizes funds, and complies with regulations.